Analisis Strategi Promosi Terhadap Minat Pengunjung Pameran Jogja International Food Expo 2025: Analysis of Promotional Strategies for Visitor Interest at the 2025 Jogja International Food Expo - Muhammad Heykal; Erisya Heriyanti; Miftahudin (OGZ Research & Publishing, 2025)
This research aims to examine how the organizers of the Jogja International Food Expo 2025 implement their promotional strategies and to identify the most effective promotional elements in attracting visitors. In an increasingly competitive environment, creative and well-targeted promotional methods are essential. This study adopts a qualitative research design. The data analysis technique applied is qualitative document analysis, which involves examining data derived from various official reports such as annual reports, activity reports, and policy documents related to promotional media for visitor engagement. The findings reveal that online media—particularly Instagram and TikTok—are the most effective promotional tools at present. These platforms offer extensive reach and can engage diverse audiences rapidly. According to the Public Relations team at Krista Exhibitions, online media, especially platforms like Instagram and TikTok, play a crucial role in attracting visitors. Through creative content such as short videos, engaging photos, and interactive stories, promotions become more appealing and are more easily received by audiences. Purpose: To identify the most effective promotional elements in attracting visitors to the Jogja International Food Expo 2025.Methodology: Qualitative research with a descriptive approach.Findings: Online media, particularly Instagram and TikTok, are currently the most effective promotional channels due to their broad reach and ability to engage audiences quickly.